Pengaruh Kualitas Sistem dan Kualitas Informasi Aplikasi Telemedicine Halodoc Terhadap Kepuasan Pengguna Pada Follower Akun Twitter @Halodocid - Ahmed Kemal Ariadanang; Dhety Chusumastuti (Jurnal Ilmiah Manajemen Informasi dan Komunikasi, 2022)
User satisfaction continues to be a top priority in terms of digital services and is a very important factor for the success of the services. Halodoc is a telemedicine with a mobile application platform whose users are increasing due to the need for information during the Covid-19 pandemic. Halodoc as a health application that has a function as a health information and consulting service in Indonesia is expected to provide good service to provide user satisfaction.In that regards, this study aims to examine the effect of system quality and information quality of Halodoc application on user satisfaction. This research was conducted based on the Information Systems Success model designed by DeLone and McLean by taking several dimensions of success or the required variables.The samples used in this study were followers of the Twitter account @HalodocID who used the Halodoc application as of 10 August 2021. Questionnaires were distributed on 19-30 August 2021.This study chose the multiple linear regression model as a data analysis method that passed five tests; those are the normality test, the linearity test, the multicollinearity test, the autocorrelation test, and the heteroscedasticity test.Prior to the five tests, all questionnaire data from respondents had been tested and declared valid and reliable.Hypothesis testing in this study was carried out by examining the effect of system quality and information quality variables on user satisfaction through simultaneous testing (F test) and partial testing (t test). The research result proves that system quality and information quality have a positive and significant effect on user satisfaction.